Visual Novel Sebagai Media Pengenalan Cerita Daerah “Ki Kures dan Naga Antaboga” Menggunakan Metode Multimedia Development Life Cycle - Aisyah, Azkiya (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2025)
Local folklore is an essential part of Indonesia's cultural heritage that must be preserved, especially in today’s digital era where young people tend to lose interest in traditional stories. This study aims to develop an interactive media in the form of a visual novel as a tool for introducing local stories through a more engaging and technologically relevant approach. The method used is the Multimedia Development Life Cycle (MDLC), consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. The visual novel is developed using technology that integrates 2D graphics, voice narration, and animations, and offers branching storylines to enhance user interaction. User testing using the User Acceptance Test (UAT) method resulted in an average user satisfaction score of 4.4 out of 5. Additionally, pre-test and post-test results showed a 79.3% increase in users' understanding of the story content. Therefore, this visual novel is not only an effective educational media alternative to reintroduce traditional stories to younger generations, but also successfully introduces the story of Ki Kures and Naga Antaboga in an engaging and modern format.